Current interventional strategy for the treatment of hepatic alveolar echinococcosis. Issue 12 (1st December 2016) - Vuitton, Dominique A.; Azizi, Amel; Richou, Carine; Vuitton, Lucine; Blagosklonov, Oleg; Delabrousse, Eric; Mantion, Georges A.; Bresson-Hadni, Solange
ABSTRACT: Introduction : The use of various types of invasive interventions combined with anti-infective drugs in the therapeutic strategy of alveolar echinococcosis (AE) has changed during the last 30 years. Areas covered : This article reviews the current respective indications of surgical, percutaneous and perendoscopic interventions in AE and proposes an integrative therapeutic strategy. Expert commentary : Hepatic resection is indicated whenever it is feasible and curative; palliative surgery should be avoided; percutaneous procedures are best adapted to the drainage of the necrotic cavity present in advanced cases; perendoscopic procedures with stenting are best adapted to alleviating the biliary complications that are common and life-threatening in AE patients. Continuous administration of albendazole or mebendazole, without interruption is mandatory in all cases, temporarily (recommended duration: 2 years) after radical lesion resection in patients without immune suppression; for life in all other cases. Long-term follow-up is essential.